Symon's dinners cooking out : 100 recipes that redefine outdoor cooking - Symon, Michael, 1969-; Trattner, Douglas (Clarkson Potter/Publishers, 2025)
"Go beyond burgers with 100 recipes for showstopping mains, salads, even desserts--all cooked outside--from the host of Symon's Dinners Cooking Out, BBQ USA, and BBQ Brawl on the Food Network. In Symon's Dinners Cooking Out, Michael Symon offers 100 recipes for barbeque, grilling, and outdoor cooking. Featuring 50 fan-favorite recipes from his popular Food Network show, Symon's Dinners Cooking Out, and 50 brand new recipes, this cookbook is sure to excite budding and expert grillers alike. From live-fire classics like Bacon-Cheddar Smash Burgers to unexpected dishes like Charred Broccoli Salad and Crispy Feta Eggs, cooks who opt to take it outside will find all kinds of creative ways to use their grills year-round paired with 100 beautiful photos shot at Michael's home in Southern California. Impress your friends with showstopping mains like Gyro-Style Lamb Burger with Tzatziki and Grilled Onion, Grilled Eggplant Parmesan, and Birria Style Beef Tacos. Round out the meal with sides like Stuffed Squash Blossoms, Duck Fat-Fried Fondant Potatoes, or Blue Cornbread with Honey Butter, and serve up salads to remember like Shaved Carrots with Yogurt Dressing, Grilled Greens with Lime Vinaigrette, or Avocado, Orange, and Jicama Salad. And of course there are desserts, too from Fresh Strawberry Pie to Chocolate Chip Cookie Bars--all cooked (you know it) outside"--